Cadastral level Soil and Water conservation Priority Zonation using Geospatial technology - Jean Joy; Shruti Kanga; Suraj Kumar Singh; Sudhanshu Sudhanshu (Hasanuddin University, 2021)
Water is the most precious commodity that human being wanted, nowadays water is depleting due to several human interventions. In Kerala state, even though high rainfall is received, still water scarcity is faced during summer and soil erosion is higher. This watershed area is prone to water scarcity during the summer season and stream network become dry during that period. This clearly indicates that human interventions and unscientific agricultural activities may be the result. In this, study GIS and RS technologies are used to find and map the Soil and water conservation priority zones, also several action Plans where proposed. SOI Topo sheet were used to digitize the contours and DEM was created using that with ArcGIS 10.2.2 software. LULC maps were digitized from satellite image and using other parameters and suitable weight values, the weighted overlay was done to find out the Priority Zones. Cadastral Plot boundaries were overlaid for plot-wise priority zones and several conservation methods like gully plugin, check dams, vegetation bund etc. were proposed.